2021
DOI: 10.15376/biores.16.2.2235-2248
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic condensation of depithed sugarcane bagasse derived levulinic acid into diphenolic acid

Abstract: Levulinic acid (LA) is a platform chemical that can be produced from biomass. Diphenolic acid (DPA) is a derivative of LA with the potential to replace bisphenol A, a plasticizer. To determine the optimum conditions for DPA production, commercial LA was used with a mild environmentally benign acid, namely, methanesulfonic acid (MsOH). The optimized reaction parameters were time (6 h), temperature (75 °C), and catalyst loading (5.5 g), yielding 65.8% DPA at 90% LA conversion. The response surface methodology (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The authors found that HCl led to the highest LA conversion (entry 3, Table 2 , 65 mol%) but also to the lowest p , p ′-DPA/ o , p ′-DPA molar ratio (2.0), whilst the sulfamic acid resulted in the most promising catalyst (entry 10, Table 2 ), showing comparable conversion but with a much higher selectivity towards the p , p ′-DPA isomer ( p , p ′-DPA/ o , p ′-DPA molar ratio of 7.4) and the yield of 51 mol%. Mthembu et al [ 33 ] optimized the Response Surface Methodology (Box–Behnken) for the condensation reaction between commercial LA and phenol by employing methanesulfonic acid as the homogeneous catalyst. The effects of the reaction time, temperature, and acid loading were investigated while keeping constant the LA/phenol molar ratio (3.7).…”
Section: Dpa Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The authors found that HCl led to the highest LA conversion (entry 3, Table 2 , 65 mol%) but also to the lowest p , p ′-DPA/ o , p ′-DPA molar ratio (2.0), whilst the sulfamic acid resulted in the most promising catalyst (entry 10, Table 2 ), showing comparable conversion but with a much higher selectivity towards the p , p ′-DPA isomer ( p , p ′-DPA/ o , p ′-DPA molar ratio of 7.4) and the yield of 51 mol%. Mthembu et al [ 33 ] optimized the Response Surface Methodology (Box–Behnken) for the condensation reaction between commercial LA and phenol by employing methanesulfonic acid as the homogeneous catalyst. The effects of the reaction time, temperature, and acid loading were investigated while keeping constant the LA/phenol molar ratio (3.7).…”
Section: Dpa Synthesismentioning
confidence: 99%
“…Only a slight decrease in the p , p ′-DPA yield up to the value of 85 mol% was observed, which was mainly attributed to some loss of the ionic liquid that occurred during the separation step. Mthembu et al [ 33 ] employed [EMIM][OTs] and [BMim]HSO 4 , considering the catalysis with H 2 SO 4 (entry 5, Table 2 ), p -TSA (entry 9, Table 2 ), and CH 3 SO 3 H (entry 11, Table 2 ), for comparison purposes. Maximum DPA yields of 59 and 68 mol% were obtained with such ionic liquids (entries 78 and 79, Table 6 ), which are comparable to those already reported for the homogeneous catalysts.…”
Section: Dpa Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…In the biological refining industry, 5-HMF is recognized as an important and renewable platform chemical. , Its derivatives include 2,5-furfuryldiamine, 2,5-furfuryldiisocyanate, and 5-hydroxymethyl furfurylidenester, all of which are excellent raw materials for the production of polymers like polyester, polyamide, and polyurethane. However, 5-HMF is unstable in acidic environments and can easily be further converted into LA. LA is also one of the top 12 bio-based platform chemicals listed by the U.S. Department of Energy and can be used to produce γ-valerolactone, succinic acid, 1,4-pentanediol, bisphenolic acid, maleic anhydride, and other chemicals. These derivatives can then be used as solvents and fuel additives or in the production of polymers, battery electrolytes, and so forth …”
Section: Introductionmentioning
confidence: 99%